Efektifitas Pelaksanaan Aplikasi Sistem Informasi Administrasi Online Masyarakat Palembang (Sidemang) di Kelurahan Oganbaru Kecamatan Kertapati Kota Palembang - Anggraini, Fitri; Sunarto, Sunarto; Wulandari, Novita (Mahesa Research Center, 2023)
This article or writing aims to effectively implement the Palembang Community Online Administration Information System Application (Sidemang) in Oganbaru Village, Kertapati District, Palembang City. The problem focuses on analyzing the level of effectiveness of implementing the Sidemang application in Oganbaru Village, Kertapati District, Palembang City as well as analyzing the supporting and inhibiting factors in using the Sidemang application. Data was collected through interviews, observations and documents related to research and analyzed qualitatively. This study concludes that the implementation of the Sidemang application in Oganbaru Village, Kertapati District, Palembang City has proven effective in producing more efficient and faster services. People are satisfied with the ease of submitting applications from home without having to come to the office. Village officials were able to adapt well to this technology. However, the continuity of this application depends on strong support from the authorities and the community. Supporting factors include telecommunications infrastructure, availability of funds, and human resources. Challenges such as unstable internet networks and paradigm changes remain obstacles that need to be overcome.